RANCANG BANGUN SISTEM INTEGRASI PUSKESMAS DAN APOTEK BERBASIS QUICK RESPONSE CODE (STUDI KASUS : PUSKESMAS GADINGREJO PASURUAN) - M. Noval Riswandha; Laili Fauziya (STMIK YADIKA BANGIL, 2021)
Abstract : Puskesmas Gadingrejo Pasuruan is one of the puskesmas that always searches for patient data in the Medical Record. The insertion of medical record cards and poor drug prescriptions resulted in data searching that took a long time. This then becomes a factor in the need for an Integrated Health Center and Pharmacy System so that the patient's medical history recording can be stored and arranged in a good mechanism. The Integrated Health Center and Pharmacy system uses the Quick Response Code method in software development. While the process of collecting data by conducting interviews with the relevant sections. This research resulted in a Quick Response Code-based Integrated Health Center and Pharmacy System which helps the relevantdepartments in recording and searching for the required patient data quickly and precisely so that medical action can be taken immediately. Keywords: Integration, Puskesmas, Pharmacy, Medical Records, Quick Response Code